2018
DOI: 10.1128/mra.00958-18
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of a Gyrovirus Associated with Ashy Storm-Petrel

Abstract: Ashy storm-petrels (order Procellariiformes) are seabirds that are found along the coast of California to Baja Mexico. A novel gyrovirus was identified from a cloacal swab of an ashy storm-petrel, which is the second gyrovirus to be identified in sea birds, the first being found in the related northern fulmar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…GyV8 was found in one northern fulmar showing ataxia and head tilt, but no other fulmar with similar clinical signs analyzed resulted positive for GyV8 [17]. ASPaGyV was discovered in cloacal samples from ashy storm petrels [19]. The presence of GyV11 was detected in three different birds from the Nouragues Natural Reserve, but only one of them was found to be positive in both cloacal and blood samples, thus supporting the idea of a possible systemic infection.…”
Section: Discussionmentioning
confidence: 70%
“…GyV8 was found in one northern fulmar showing ataxia and head tilt, but no other fulmar with similar clinical signs analyzed resulted positive for GyV8 [17]. ASPaGyV was discovered in cloacal samples from ashy storm petrels [19]. The presence of GyV11 was detected in three different birds from the Nouragues Natural Reserve, but only one of them was found to be positive in both cloacal and blood samples, thus supporting the idea of a possible systemic infection.…”
Section: Discussionmentioning
confidence: 70%
“…Gyroviruses occur in mammals and birds; in mammals, the source of detection is typically the feces, while in birds, gyroviruses can also be detected in tissue samples [35]. With the exception of chicken anemia virus (Gyrovirus chickenanemia), which is an immunosuppressive agent in chicken, other gyrovirus species are not known to cause diseases in the avian host species in which they have been identified, or the putative pathologic findings have yet to be confirmed [36][37][38][39][40][41][42][43]. In this study, we identified gyrovirus genomic traits in 12 sample pools originating from 5 counties between 2008 and 2011.…”
Section: Discussionmentioning
confidence: 99%
“…CAV is found worldwide and causes significant mortality among chicks not protected by maternal antibodies. Other gyroviruses have been identified in diseased avian hosts, including in seabirds (15)(16)(17)(18)(19). Herein, we describe a new gyrovirus associated with RDS in yellow-eyed penguins.…”
Section: Introductionmentioning
confidence: 95%
“…To infer the evolutionary history of yellow-eyed penguin gyrovirus, we estimated phylogenetic trees for both VP1 and VP2 among other known gyroviruses using Torque teno virus 1, a nongyrovirus member of the Anelloviridae, as an outgroup (Figure 3). Within VP1, yellow-eyed gyrovirus clustered with Gyrovirus 8, which caused disease in the northern fulmar, while VP2 fell within a clade of gyroviruses infecting seabirds, including Ashy storm-petrel gyrovirus (16). We next inferred the phylogeography of all full and partial yellow-eyed gyrovirus genomes obtained (34 of 43 samples) across the three sampling sites (Figure 4).…”
Section: Genome Organisation and Phylogenetic Characterisation Of A N...mentioning
confidence: 99%